Optimizing Islamic Education Learning Outcomes through the Two Stay Two Stray Method with Question Board - Nasrullah, Yufi Mohammad; Ainissyifa, Hilda; Asfiya, Syifa Nuril; Fatonah, Nurul; Nazib, Fiqra Muhamad; Shahril, Mohd Izwan (Atthulab: Islamic Religion Teaching and Learning Journal, 2024)
This research aims to measure the effectiveness of this learning method in increasing students’ understanding of the subject matter and gaining insight into students’ perceptions of the learning experience. In this research, the TSTS methods are used as learning approaches that focus on active involvement, collaboration and critical thinking of students. Question board media is used to support the visualization of abstract concepts in Islamic Religious Education. Data was collected through comprehension tests, observation, pretest and posttest. The research results show that the TSTS learning methods using question boards have a positive impact on students’ understanding. The test scores show that there is a significant effect before and after implementing this method. Where the result obtained is that tcount > ttable (4.30 > 2.06) so that H0 is rejected and Ha is accepted. So it can be concluded that there is a significant difference in the learning outcomes of Islamic Religious Education between the Pretest and Posttest for class XII social science 1 students at Asshiddiqiyah High School. Penelitian ini bertujuan untuk mengukur efektivitas metode pembelajaran ini dalam meningkatkan pemahaman siswa terhadap materi pelajaran dan memperoleh wawasan persepsi siswa terhadap pengalaman belajar. Dalam penelitian ini, metode TSTS digunakan sebagai pendekatan pembelajaran yang menitikberatkan pada keterlibatan aktif, kolaborasi dan berpikir kritis siswa. Media papan soal digunakan untuk menunjang visualisasi konsep-konsep abstrak dalam Pendidikan Agama Islam. Pengumpulan data dilakukan melalui tes pemahaman, observasi, pretest dan posttest. Hasil penelitian menunjukkan bahwa metode pembelajaran TSTS menggunakan papan soal memberikan dampak positif terhadap pemahaman siswa. Nilai tes menunjukkan terdapat pengaruh yang signifikan sebelum dan sesudah penerapan metode ini. Dimana hasil yang diperoleh adalah thitung > ttabel (4,30 > 2,06) sehingga H0 ditolak dan Ha diterima. Jadi dapat disimpulkan terdapat perbedaan yang signifikan hasil belajar Pendidikan Agama Islam antara Pretest dan Posttest siswa kelas XII IPS 1 di SMA Asshiddiqiyah.